Exendins and exendin analogs for diabetic therapy: a patent review (2012-2015). (2nd July 2016) - Park, Eun Ji; Lim, Sung Mook; Lee, Kang Choon; Na, Dong Hee
ABSTRACT: Introduction : Since exendin-4 (exenatide) was approved for diabetes therapy in 2005, several exendin analogs have been developed for the treatment of type 2 diabetes mellitus. As exenatide is a relatively short-acting injectable agent, major approaches have focused on developing long-acting exendin analogs to improve patient compliance and convenience. Areas covered : In this review, the authors report on patents related to exendins and exendin analogs from 2012 to 2015. The patents have been divided into three categories based on the technologies used to develop the new chemical entities: 1) chemical bioconjugate analogs; 2) recombinant fusion protein analogs; and 3) multifunctional peptide analogs. Expert opinion : Recently, research on exendins and their analogs has grown significantly, leading to the development of long-acting analogs and multifunctional peptides. While long-acting injectable agents are still the major products in the pharmaceutical industry, a significant growth is expected in the development of orally available exendins.